Ecological Imperialism and Literary Counter-Discourses with Special Reference to Amitav Ghosh’s ‘The Living Mountain’ - Thippeswamy M., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This paper examines Amitav Ghosh’s “The Living Mountain: A Fable for Our Times” to understand the interconnections between colonialism and climate change. Ghosh’s narrative explores the brutality, systematic exploitation of nature as well as indigenous naïve people’s lives, and the impacts of colonial expansion on the environment, revealing a historical continuity that links colonial practices with the contemporary climate crisis. By employing an ecocritical framework, the paper analyses how Ghosh critiques colonialism’s destructive impact on nature and challenges modern readers to reconsider the long-term environmental consequences of imperialist endeavours. The paper further delves into how the novella depicts human relationships with nature and advocates a symbiotic coexistence.
Keywords: Environmental Concerns; Naïve Local People; Clash Between Adepts; Anthropoi; Colonialism